2021
DOI: 10.3389/fphys.2021.678974
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Genes as Exploratory Biomarkers in DMD: Results From Both the mdx Mouse Model and Patients

Abstract: Duchenne muscular dystrophy (DMD) is a rare genetic disease due to dystrophin gene mutations which cause progressive weakness and muscle wasting. Circadian rhythm coordinates biological processes with the 24-h cycle and it plays a key role in maintaining muscle functions, both in animal models and in humans. We explored expression profiles of circadian circuit master genes both in Duchenne muscular dystrophy skeletal muscle and in its animal model, the mdx mouse. We designed a customized, mouse-specific Fluidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…The loss of dystrophin in DMD, with the absence of its tethering to an intracellular actin skeleton network, could thus interrupt sarcolemma-cytoskeleton linkage to prevent SRF-mediated signal activation in myofiber which attenuates circadian clock function [99]. In mdx mice and DMD patients, gene expression analysis revealed that Bmal1, Cry1, and Cry2 were downregulated in the dystrophic muscles, together with altered myogenic pathway involving MyoD and myogenin [101]. Furthermore, the loss of dystrophin-mediated ECM-cytoskeleton linkage in the mdx mice was found to disrupt clock entrainment [102].…”
Section: The Role Of the Circadian Clock In Muscular Dystrophy Etiolo...mentioning
confidence: 99%
See 1 more Smart Citation
“…The loss of dystrophin in DMD, with the absence of its tethering to an intracellular actin skeleton network, could thus interrupt sarcolemma-cytoskeleton linkage to prevent SRF-mediated signal activation in myofiber which attenuates circadian clock function [99]. In mdx mice and DMD patients, gene expression analysis revealed that Bmal1, Cry1, and Cry2 were downregulated in the dystrophic muscles, together with altered myogenic pathway involving MyoD and myogenin [101]. Furthermore, the loss of dystrophin-mediated ECM-cytoskeleton linkage in the mdx mice was found to disrupt clock entrainment [102].…”
Section: The Role Of the Circadian Clock In Muscular Dystrophy Etiolo...mentioning
confidence: 99%
“…New cistromic analysis revealed that components of the Igf-1 and integrin-associated signaling pathways are direct transcriptional targets of the molecular clock network [28,154]. Given that distinct clock transcriptional outputs are known DMD therapeutic targets [101,154], testing potential synergistic actions of clock-targeting interventions to promote muscle mass, function, regenerative repair, and sarcolemma stability may present unique opportunities for DMD drug development. Mechanistic insights garnered from genetic loss-of-function models suggest that reinforcement or activation of clock function may mitigate dystrophic pathophysiology [24,25].…”
Section: Recent Progress In Discovering Circadian Clock Modulators Wi...mentioning
confidence: 99%